Ocular scedosporiosis in an immunocompetent host - Ashish Bajaj; Bibhabati Mishra; Archana Thakur; Poonam Sood Loomba; Abha Sharma (Wolters Kluwer Medknow Publications, 2020)
Scedosporium apiospermum infection in humans is rare. Fungal keratitis is the most common manifestation of S. apiospermum infection in immunocompetent individuals. S. apiospermum is a filamentous fungus found in soil and polluted water. Strong suspicion of fungal keratitis should be made in all corneal ulcers with a history of trauma with vegetative matter or soil. Here, we present a case of fungal keratitis caused by S. apiospermum in an immunocompetent host.